Analytical Strategies for the Determination of Arsenic in Rice - Bruno E. S. Costa; Luciana M. Coelho; Cleide S. T. Araújo; Helen C. Rezende; Nívia M. M. Coelho (Journal of Chemistry)
Arsenic is an element of concern given its toxicological significance, even at low concentrations. Food is a potential route of exposure to inorganic arsenic and in this regard arsenic in rice is associated with soil contamination, fertilizer application, and the use of arsenic-containing irrigation water. Therefore, there is a need to investigate the regional rice crops with a view to future discussions on the need for possible regulatory measures. Several studies have reported high concentrations of arsenic in rice grown in soils irrigated with contaminated water; however, procedures used, including sample pretreatment and preconcentration steps, have to be followed to ensure sensitivity, accuracy, and reproducibility. Arsenic is a difficult element to measure in complex matrices, such as foods, because the matrix must be destroyed at an elevated temperature without the loss of the analyte or contamination. This review summarizes the major methods for the determination of arsenic in rice samples. The main purpose of this review is to provide an update on the recent literature concerning the strategies for the determination of arsenic and to critically discuss their advantages and weaknesses. These difficulties are described along with recent developments aimed at overcoming these potential issues.